Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) International Conference, October 27–29, 2016, Tomsk, Russia [proceedings] - Zykova A. P. Anna Petrovna; Martyushev N. V. Nikita Vladimirovich (2017, 2017)
Title screen